2013
DOI: 10.1021/am402845d
|View full text |Cite
|
Sign up to set email alerts
|

Highly Populated and Nearly Monodispersed Nanosilica Particles in an Organic Medium and Their Epoxy Nanocomposites

Abstract: An organic aminopropyl-functionalized nanosilica sol was synthesized in the presence of ethyl silicate, γ-(aminopropyl)triethoxysilane (KH550), and N,N-dimethylformamide (DMF) via a sol-gel technique and then used to prepare epoxy nanocomposites. Structure and morphology analyses of the obtained aminopropyl-functionalized nanosilicas were observed by dynamic light scattering (DLS), transmission electron microscopy (TEM), and high-resolution TEM (HRTEM). TEM and DLS showed that modified nanosilicas with an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…T g characterizes the chain segmental mobility which is determined mainly by the chemical structure and also is related to the interfacial interaction for nanocomposites. The T g variation of epoxy nanocomposites is proposed to be a result of two competitive factors: the enhanced interaction and the decreased cross‐linking density of epoxy . Compared with the unmodified HNTs, the enhanced interaction between the A‐HNTs and epoxy restricted the motion of chain segments.…”
Section: Resultsmentioning
confidence: 99%
“…T g characterizes the chain segmental mobility which is determined mainly by the chemical structure and also is related to the interfacial interaction for nanocomposites. The T g variation of epoxy nanocomposites is proposed to be a result of two competitive factors: the enhanced interaction and the decreased cross‐linking density of epoxy . Compared with the unmodified HNTs, the enhanced interaction between the A‐HNTs and epoxy restricted the motion of chain segments.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past few decades, tremendous efforts have been made and different kinds of modiers have been developed to improve the toughness of epoxy resins, such as liquid rubber or rubber particles, 5,6 thermoplastics, 7 and nanoparticles. [8][9][10] In most cases, blending modiers into the epoxy matrix brings about the improvement of toughness but oen signicantly compromises the thermal properties, 11,12 modulus and strength of the resins. 13,14 Moreover, phase separation before or during the curing process aer incorporation of these modiers may result in great difficulty in the design of interfacial chemistry and cure schemes to guarantee a proper morphology of the cured networks.…”
Section: -4mentioning
confidence: 99%
“…3(b), as the HBPSi-2 loading increases from 0% to 15%, T g of E-HBPSi-2 decreases stepwise. Various research groups [37][38][39][40][41][42] have reported a decrease in T g when silica or organosilicone are added to epoxy or some other matrix. Generally, this behavior has been attributed to plasticizing effect or to a limited amount of unreacted reactant.…”
Section: Dma Characterizationmentioning
confidence: 99%
“…이러한 이유로 에폭 시 복합재료의 내충격성 및 열안정성을 개선하기 위 한 다수의 연구가 진행되고 있다. 에폭시 수지에 보다 유연한 물성의 고무, PMMA계(Polymethylmethacrylate) 코어-셀(core-shell), CTBN (carboxyl terminated acrylonitrile butadiene)과 같은 탄성체를 도입하거나 [2], 나노 클레이(Montmorillonite, MMT) [4], 탄소나노튜브(Carbon Nano Tube, CNT) [5][6][7], HNT (Halloysite Nano Tube) [8,9], Carbon [10], SiO2 [11][12][13] Figure 5에 neat epoxy, epoxy/CA0030_70%, epoxy/ CA0030+APTES2%_70%, CA0030, CA0030+APTES 2% 를 TGA thermogram을 나타내었다. …”
Section: 서 론unclassified